CORRELATION BETWEEN CREATIVE THINKING, SELF-ESTEEM, AND ATTITUDE TOWARDS TECHNICAL AND VOCATIONAL EDUCATION AMONG STUDENTS IN ENUGU STATE - Ogbonna, Dennis (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The present study investigated secondary school students' attitudes towards TVE based on creative thinking and self-esteem. One hundred and sixty-six secondary school students drawn from public and private secondary schools in Enugu State participated in the study. The participants completed self-report measures on attitude towards TVE, creative thinking assessment, and Rosenberg's self-esteem scale. The findings revealed that 65.5% of the respondents expressed a positive attitude towards TVE. Also, a multiple regression model was computed to test the study's hypothesis. The regression test results showed that creative thinking and self-esteem had a positive relationship with attitudes toward TVE, as indicated by the value of (r = 0.47, F = 41.13, p<0.01). Creative thinking and self-esteem jointly explained about 21.2% of the variation in attitudes towards TVE.